2011
DOI: 10.1002/cm.20525
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flagellar cysteine‐rich sperm proteins involved in motility, by the combination of cellular fractionation, fluorescence detection, and mass spectrometry analysis

Abstract: Mammalian sperm proteins undergo thiol group (SH) oxidation to form disulfides bonds (SS) as they travel through the epididymis during cell maturation. Disulfide bonds are involved in chromatin condensation and tail organelle stabilization. In this work, we used a fluorescent thiol-selective labeling agent, monobromobimane (mBBr), to study the protein thiol status of rat sperm during maturation. Fluorescence signal decrease along the epididymal trip, more evidently in the head, but also in the tail, indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Free cysteine levels are an indirect marker of the number of disrupted disulphide bonds, as despite not all free cysteine radicals resulting from the breakage of disulphide bonds, a significant percentage has this origin (Yeste et al, 2013. Specifically, disulphide bonds are crucial for a protein associated with the outer dense fibre 1 (ODF1; Cabrillana et al, 2011). Another issue is the observed increase in free cysteine residues in sperm tail extracts during IVC and the melatonin-counteracting effect of that increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free cysteine levels are an indirect marker of the number of disrupted disulphide bonds, as despite not all free cysteine radicals resulting from the breakage of disulphide bonds, a significant percentage has this origin (Yeste et al, 2013. Specifically, disulphide bonds are crucial for a protein associated with the outer dense fibre 1 (ODF1; Cabrillana et al, 2011). Another issue is the observed increase in free cysteine residues in sperm tail extracts during IVC and the melatonin-counteracting effect of that increase.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is the observed increase in free cysteine residues in sperm tail extracts during IVC and the melatonin-counteracting effect of that increase. Thus, it could be hypothesised that changes in the number of disrupted disulphide bonds along the flagellum, specifically in flagellum-bond-related proteins such as sperm hexokinase-1 (Cabrillana et al, 2011(Cabrillana et al, , 2016, could also be related to the changes in motion parameters observed during IVC. Specifically, disulphide bonds are crucial for a protein associated with the outer dense fibre 1 (ODF1; Cabrillana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within spermatozoa, disulfi de bond formation occurs in both the head, particularly in nuclear protamines as part of sperm chromatin condensation, as well as within the sperm tail [ 95 ]. The sulfhydryl rich organelles in the sperm tail that undergo oxidation to disulfi des include the outer dense fi bers, including the protein outer dense fi ber 1, connecting piece, outer mitochondrial membranes, and the fi brous sheath [ 96 ]. Disulfi de bond formation is thought to be important for sperm motility maturation since incubation of spermatozoa with a sulfhydryl-specifi c membrane impermeant dye inhibited the motility of goat spermatozoa [ 97 ].…”
Section: Disulfide Bond Formationmentioning
confidence: 99%
“…By labelling epididymal spermatozoa with sulfhydryl compounds such as [N-3 H]ethylmaleimide (Miller and Masui 1982), N-(4-carboxy-3-hydroxy-phenyl) maleimide (which forms fluorescent adducts) (Mercado et al 1976) and [ 14 C]iodoacetamide, it is clear that nuclear protein thiol oxidation occurs during epididymal transit, which is likely to be a reflection of the redox status of protamines (Shalgi et al 1989). In addition, others have shown that cysteine oxidation occurs within the outer dense fiber 1 protein (ODF1) (Cabrillana et al 2011) and hexokinase (HK1) (Nakamura et al 2008) as sperm descend the epididymis. ODF1 is a chaperone and, as such, its redox status may help in the folding of various proteins as well as in the elastic recoil of the sperm tail (Morales et al 1994).…”
Section: Disulfide Bond Formationmentioning
confidence: 97%